Policy implications for offshore renewable energy in Australia: An MSP approach supporting the energy transition - Laura L. Griffiths; Camille Goodman; Michelle Voyer; Jackson Stockbridge; Anna Lewis; Freya Croft; Chris LJ. Frid (Energy Policy, 2025)

Rethinking blue economy governance – A blue economy equity model as an approach to operationalise equity - Freya Croft; Hugh Breakey; Michelle Voyer; Andrés Cisneros-Montemayor; Ibrahim Issifu; Makrita Solitei; Catherine Moyle; Brooke Campbell; Kate Barclay; Dominque Benzaken; Hekia Bodwitch; Leah Fusco; et al. (Environmental Science & Policy, 2024)

Global blue economy governance – A methodological approach to investigating blue economy implementation - Lucky Wuwung; Freya Croft; Dominique Benzaken; Kamal Azmi; Camille Goodman; Constance Rambourg; Michelle Voyer (Frontiers in Marine Science, 2022)
The proliferation of the blue economy in political discourse has gained traction in recent years, however, there remains no standardized definition. The triple bottom line goals of economic development, social equity, and environmental conservation are at the center of the blue economy vision. Yet the ambiguities surrounding the term have resulted in considerable variation in how the blue economy is implemented and what is prioritized. This paper takes a global snapshot of current approaches to national level blue economy governance. In doing so this paper provides the first global assessment of blue economy implementation approaches, through the development of a global blue economy database. Using the best available information from policy documents, media releases and other publicly available online information, we comparatively analyzed each country’s governance strategy to assess the level of blue economy development in coastal states around the world. Throughout this paper we outline the novel methodological approach we took in order to develop a tool for analyzing national level blue economy implementation on the global scale. This approach will allow for ongoing and continued analysis of blue economy operationalization as the concept continues to evolve.